Rancang Bangun Sistem Informasi Manajemen Event berbasis Web - Faesal Herlambang; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
An event must be adapted so that it still can be held on a pandemic situation. Because it involves many people, the implementation of events during a pandemic must be done using online media to avoid direct physical contact. Therefore the process of managing an event must also be done using online media. Generally, the documentation of managerial process on an events is not done centrally or under the same roof, including assignments to each organizing committee. This can cause problems if there is miscommunication between parties, causing delays in the managerial event process. Especially when using online media. Therefore, a web-based event management information system was developed to help resolve these problems. This research was developed using the waterfall method because it is easy and suitable for building generic systems. The system developed has 77 functional requirements and 3 types of actors. This system is written on a web platform, using the JavaScript programming language and the help of the ReactJS library. Then MongoDB is used as a database service provider and is linked to the system using GraphQL. The testing phase was carried out using the white box and black box methods for the functional systems which all passed the test.